Effects of continuous Hormone Replacement Therapy (HRT) on FSH, lipid profiles, blood chemistry, and skin thickness in menopausal women (Faculty of Medicine Universitas Indonesia, 2002)
This study was aimed to observe the effect of hormone replacement therapy (HRT) of estradiol 2 mg + 1 mg acetate noretisterone administered continuously on FSH hormone, lipid profile, blood chemistry, and skin thickness in menopausal women. The duration of HRT administration was 6 months. The subjects of the study were 35 menopausal women. The study was conducted from January 2001 to June 2001. After HRT administration of 6 months, a significant decrease of FSH was observed. No effect of HRT was found in bilirubin level; however, there was a slight increase of alkali phosphatase enzyme, and a signifcant increase in SGOT and SGPT. HRT caused a decrease of total cholesterol level and triglyceride level. In addition, a slight increase of LDL level and significant decrease of HDL level were observed. HRT administration with progesterone synthetic noretisterone showed an increase of skin collagen synthesis, which was indicated by the significant increase of skin thickness. (Med J Indones 2002; 11: 97-103)Keywords: HRT, FSH, menopause, lipid profile, blood chemistry, skin thickness